2007
DOI: 10.1002/jbm.a.31649
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemistry influences implant‐mediated host tissue responses

Abstract: Implant-mediated fibrotic reactions are detrimental to the performance of encapsulated cells, implanted drug release devices and sensors. To improve the implant function and longevity, research has emphasized altering cellular responses. Although material surface functional groups have been shown to be potent in affecting cellular activity in vitro and short term in vivo responses, these groups appear to have little influence on long-term in vivo fibrotic reactions, possibly as a result of insufficient interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(106 citation statements)
references
References 55 publications
7
99
0
Order By: Relevance
“…Consistent with our previous study, 55 the fibrous capsule around the implants varied significantly among the three different functional groups represented. In general, the particles containing the -OH groups exhibited the thickest capsule formation, followed by the polypropylene control particles, which consist predominately of the -CH 2 functionality.…”
Section: Surface Functionality Influences Fibrotic Capsule Formationsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with our previous study, 55 the fibrous capsule around the implants varied significantly among the three different functional groups represented. In general, the particles containing the -OH groups exhibited the thickest capsule formation, followed by the polypropylene control particles, which consist predominately of the -CH 2 functionality.…”
Section: Surface Functionality Influences Fibrotic Capsule Formationsupporting
confidence: 91%
“…In fact, our studies have found that surface functionality has significant influence on inflammatory cell accumulation (or inflammatory responses), but limited effect on fibrotic tissue reactions. 42,43,55 To test this hypothesis, it is essential to increase the interactions between functional groups and cells by increasing the surface area and/or density of functional groups. Spherical particles were chosen for this purpose to maximize the surface to volume ratio of the implants and also to mimic drug release particles and highly porous tissue scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…81,183 Since then, a lot of effort has been directed towards improving the purification of polymers, the standardization of methods and better fundamental understanding of the biocompatibility of capsules and interactions with host soft tissues. 184,185 Nevertheless, the in vivo stability of electrostatic and hydrogen bonds maintaining the structure of microcapsules is limited, and the mechanical resistance of capsules is still a concern. Liquidcore/shell microcapsules generally seem to allow better cell growth and protein production, although their mechanical resistance is further diminished compared to matrix-core capsules.…”
Section: Resultsmentioning
confidence: 99%
“…After anesthesia, rabbit bone marrow was collected into a 10-mL syringe that contained 5000 U of heparin. The marrow was resuspended in a 0.84% NH 4 Cl solution. After 5 min, approximately 2.0 · 10 6 marrow cells were plated in a 25-cm 2 plastic flask in Dulbecco's modified Eagle medium (DMEM), which was supplemented with 10% fetal bovine serum (FBS; Hyclone Laboratories), 2 mM l-glutamine, 100 U/mL penicillin, and 0.1 mg/mL streptomycin.…”
Section: Isolation Culture and Expansion Of Rabbit Mscsmentioning
confidence: 99%
“…These factors include the roughness of the material interface, hydrophilicity, stress distribution, surface charge distribution, the density and strength of biological ligands, and the local microstructure. 4,5 The biology of chondrocytes is highly influenced by their interactions with specific extracellular matrix (ECM) molecules. 6 In recent years, the principle of surface modification has been utilized to mimic the interaction between ECM proteins and their surrounding cells.…”
Section: Introductionmentioning
confidence: 99%